Língua e ensino em contexto de diversidade linguística e cultural: o caso de Guiné-Bissau - Virginia Jose Baptista Ca (2015)
The issue of the language in which literacy occurs has been and it always will be one of the major limitations in the Guinean education system. The language to be used to teaching at schools causes controversy (AUGEL, 2006). In a society like Guinea-Bissau, many people think that the written language has more value than the other forms of interaction, as in the case of mother tongues that are organized in orality, as organize and store human knowledge. The languages expressed only by orality are undervalued by the elites and by the Government. Many Guinean students have difficulties in learning Portuguese Language at schools. In most cases, children learn Portuguese at school and (but) elsewhere, they speak their mother tongues. If one takes into account the high number of children of different mother tongues, it may be surprised by the diversity of cultures in the classroom, in the country. In the other hands (However), this diversity (that could be positive) becomes an obstacle to the success of the Portuguese language taught at schools. If it is considered that the child learns best in the language that dominates, it wouldn't be important have a teacher speaking the language of the student during the teaching-learning process? (UNESCO, 1951). In this sense, this research proposal, assuming a qualitative study of exploratory, and aims to investigate the literacy practices delivered by teachers in their speeches, considering the linguistic and cultural diversity of Guinea (FREIRE, 1978). An exploratory study was conducted with two schools, one public and one school in Self-management scheme, with 1st class teachers, composed by observation of classroom, materials analysis and semi-structured interviews with six teachers from the initial degrees, including one director and one pedagogue of the Basic Education School. From the collected data it was found that, in both schools, the mother tongues are silenced by the Portuguese, the official language. In the public school, the class is given in a bilingual mode: the Creole language is used as a way for understanding the Portuguese language in the classroom. In interviewing teachers and in observing two schools, it was noticed that there is a strong tension between the official language and the national language, while we can say that in both schools, there is a presence of the Creole language in interactions between students. The reality of these students leads to the conclusion that is important that the teaching-learning process occurs in multilingual context (DIALLO, 1996).